Storyworlds across Media : Toward a Media-Conscious Narratology. - Ryan, Marie-Laure (Frontiers of narrative., 2014)
The proliferation of media and their ever-increasing role in our daily life has produced a strong sense that understanding media-everything from oral storytelling, literary narrative, newspapers, and comics to radio, film, TV, and video games-is key to understanding the dynamics of culture and society. Storyworlds across Media explores how media, old and new, give birth to various types of storyworlds and provide different ways of experiencing them, inviting readers to join an ongoing theoretical conversation focused on the question: how can narratology achieve media-consciousness?